Equity in learning paths and contrast to early school leaving: the complexity of the factors involved in the school experiences of foreign students - Bembich, Caterina (Frontiers in Education, 2023)
The European guidelines and orientation in recent years have been focus on the promotion of equity in the learning paths and in the counteract early school leaving. Although many actions to reduce early school leaving have been implemented, today there remain many students who fail to achieve satisfactory school outcomes, especially among students with a migrant background (Suárez-Orozco et al., 2010). To understand the dynamics that can lead students in conditions of fragility towards negative educational paths, it is necessary to employ a complex and multidimensional analytical framework (Bronfenbrenner & Morris, 2007). Starting from these premises, this study aims to explore the impact of individual and contextual factors in the learning pathways of foreign-born students, taking the students' perspective. 244 students attending the second level of secondary school answered to a survey, which explores their perception about: the meaning attributed to the school; the role of teachers and the family in supporting their learning path; their involvement in extra scholastic activities. The results highlight the inclusive role play by the school, which represent a place for integration into the community for foreign students; the central role of relationship with teachers and the emotional support received by the family, in counteracting early school living; the participation of students with a migratory background in their extra scholastic activities as element of protection. The results suggest that to respond to foreign students' complex educational needs, school cannot act as an isolated entity, but rather should build networks that involve families and external contexts.